Methods of perturbation theory in the qualitative essential spectral analysis of differential operators - Erovenko, V. A. (Mathematical Modelling and Analysis, 1998)
The qualitative properties of perturbed differential equations are investigated. The analogies of the classical Weyl theorem are proved.First Published Online: 14 Oct 2010